Phosphorescent iridium-containing nanomicelles: synthesis, characterization and preliminary applications in nanomedical imaging. Issue 59 (4th October 2018) - Monaco, I.; Maturi, M.; Matteucci, E.; Locatelli, E.; Baschieri, A.; Zani, P.; Armanetti, P.; Menichetti, L.; Sambri, L.; Comes Franchini, M.
Abstract : We propose a biocompatible nanoparticle made from an intrinsically phosphorescent copolymer, synthesized directly with an imaging tag present on its backbone. Abstract : Diagnostic nanomedicine constantly requires the development of novel contrast agents with intrinsic imaging capabilities. Phosphorescent Ir(iii )-complexes represent good candidates when delivered through polymeric nanoparticles. In this work, we propose a biocompatible nanoparticle made from an intrinsically phosphorescent copolymer, synthesized directly with an imaging tag present on its backbone. Polymeric nanoparticles can be obtained with the exact amount of phosphorescent moieties needed to maximize their output signal. Complete characterization and ex vivo studies confirmed that this nanosystem is suitable as a future diagnostic tool.